Overcoming the horrors of perinatal obsessive-compulsive disorder : stories of lived experience and recovery : a thesis presented in partial fulfilment of the requirements for the degree of Master of Health Science in Psychology at Massey University, Auckland, New Zealand - Francis, Astastia (Massey University, 2023)
Perinatal populations are vulnerable to the development and exacerbation of obsessive compulsive disorder (OCD). Perinatal OCD can be highly debilitating and interfere with the experience of motherhood if left untreated. Despite this, research investigating treatment and recovery experience remains sparse. This study explored the lived experience of perinatal OCD and recovery to gain an understanding of the treatments and strategies that can facilitate recovery. Data was collected from a secondary source ‘The OCD Stories’ podcast. Podcast transcripts were analysed using interpretative phenomenological analysis to enable rich and nuanced insights into lived experience. The first research objective explored how mothers experienced perinatal OCD, and the meaning that was assigned to these experiences. The overarching theme ‘Stuck in a horror story’ illustrated the terrifying, tormenting, and destructive nature of perinatal OCD. The second research objective explored the experience of treatment and recovery. The overarching theme ‘An arduous but worthwhile road to recovery’ identified the multiple recovery strategies that were used to overcome the disorder and challenges that were experienced along the way. The final overarching theme ‘Words of Hope’ illuminated that hope is central to recovery. Overall, these findings demonstrated that recovery from perinatal OCD is possible. These findings add to small body of literature on perinatal OCD and emphasise the importance of early identification and treatment within clinical settings.
Keywords: 520304 Health psychology